THE GOVERNMENT'S ROLE IN OVERCOMING UNDERAGE MARRIAGE IN THE MUSLIM COMMUNITIES - Suprijati Sarib; M. Alimashariyanto; Rahmah Nur; Ade Irma Imamah; Rahmawaty Rahmawaty (Jurnal Pembaharuan Hukum, 2023)
This research aims to analyze the government's role in overcoming underage marriage in the Muslim communities in Manado City, North Sulawesi Province, Indonesia. The government's involvement is significant because of the yearly increase of child marriage cases in the city. Therefore, this qualitative research employed a descriptive approach to analyze the data, which were collected through observation, interviews, and documentation. The primary data sources were the heads of the Religious Affairs Offices in Manado City, consisting of the Tuminting, Tikala, Wenang, and Singkil Subdistricts, while journal articles, government regulations, literature, and other relevant documents constituted the secondary data. Subsequently, the results showed that the government's duties and functions concerning marriage in the city are implemented through the Religious Affairs Office and include providing services, monitoring, recording, reporting, and guidance. Its role in combating underage marriage in the city's Muslim community is performed through formal activities, namely the socialization of Act No. 16/2019 concerning the age of marriage, pre-marital guidance and education for school-age children and millennial youth, as well as marriage preparation guidance. Also, non-formal activities are performed through lectures, coaching, and rendering marriage advice at the majlis ta'lim and youth events in mosques.